Simulation of Micro-Precoating Effect on Temperature Distribution in Plasma Thermal Spraying (Journal of Coating Science and Technology, 2018)
The effect of micro-precoating on temperature distribution of the plasma thermal spraying was simulated. After the plasma thermal spraying test with SS304 as precoating, the effect of micro-precoating on the wear loss and fatigue had been studied preliminarily. Results show that the surface temperature with micro-precoating is higher than that of without micro-precoating. Meanwhile, the heat affected zone with precoating is wider which effectively restrains the microcracks forming in the succedent coating. Subsequently, the wear and fatigue of the plasma thermal spray coating are significantly increased with the optimum micro-precoating thickness.